## Smart Fallacies: i=1, 1= 2 and 1= 3

This mathematical fallacy is due to a simple assumption, that $ -1=\dfrac{-1}{1}=\dfrac{1}{-1}$ . Proceeding with $ \dfrac{-1}{1}=\dfrac{1}{-1}$ and taking square-roots of both sides, we get: $ \dfrac{\sqrt{-1}}{\sqrt{1}}=\dfrac{\sqrt{1}}{\sqrt{-1}}$ Now, as the Euler's constant $ i= \sqrt{-1}$…

Premsagar Chauhan:Thanks, sir that is nice explanation about ensemble. I have…view comment →

Aryan:Hi , currently one more website which is going trending…view comment →

Josh McLaglen:Having anInstagram account with lots of followers is not an…view comment →

diugu:asview comment →

Sweety:Unable to understandview comment →